Determination of Bolus Dielectric Constant for Optimum Coupling of Microwaves through Skin for Breast Cancer Imaging - Carey Rappaport (International Journal of Antennas and Propagation)
We find the complex dielectric constant of the bolus liquid with the best microwave impedance match to skin-covered fatty breast tissue. The real dielectric constant and conductivity of the ideal medium are determined by minimizing the magnitude of the reflection coefficient from the two-interface frequency-dependent system, using published measured skin and breast fat dielectric characteristics in the 400 MHz to 10 GHz frequency range. Error bounds are provided to indicate the coupling degradation when using real, nonideal media for the bolus liquid. Two frequency regimes are identified. Below 6.45 GHz, conventional liquid mixtures can approach the optimal coupling permittivity, but the reflection magnitudes for these best cases are high. Above 6.45 GHz, perfect coupling is possible, but only for impractically high values of bolus dielectric constant and loss.